Cerebral palsy: comorbidities, the second hidden side - Desouza, Jinela; Patil, Mohan; S., Yamini; Kurane, A. B. (International Journal of Contemporary Pediatrics, 2020)
Background: Cerebral palsy (CP) is the most common group of permanent disorders of motor impairment resulting from injury in the developing brain which are accompanied by comorbidities. Moreover, it has been observed that because of physical disabilities, the underlying comorbidities are neglected. The study aimed to assess the co-morbidities in children suffering from cerebral palsy in Kolhapur district. Methods: The cross-sectional study was conducted among children suffering from cerebral palsy and presenting to Department of Paediatrics (n=250), D. Y. Patil Medical College, between October 2018 to October 2019. Detailed history with clinical examination were recorded in a pre-designed performa. The patients were classified according to the physiological and topographical classification. Data was analyzed using R software version 3.6.1. Variables were represented using frequency distribution, (p<0.05). Results: Of the total participants (n=250), male predominance was observed (n=140); with age range of 1-18 years. Common form of cerebral palsy was spastic type (n=140; 56%). Most common type among spastic CP was diplegia (n=96; 38%). Children were suffering from speech abnormality in spastic CP cases (n=65). Among spastic hemiplegic cases all the children were suffering from intellectual disability (n=3). Conclusion: Thus, it can be concluded that the motor impairment in just the top notch, the actual disability is the underlying co morbidities.